Hydrogeological condition patterns of Kuznetsk Basin coalbed methane fields for estimating hydrodynamic calculations - Gridasov, Alexander; Kuzevanov, Konstantin Ivanovich; Bogdanova, Anna Gennadievna (IOP Publishing, 2016)
The paper describes the natural regional conditions and key formation factors of groundwater dynamics. Characteristic hydrogeological structure elements for Kuznetsk Basin coal were identified providing parameter-oriented hydrodynamic calculations and hydrogeological models in predicting coalbed methane mining impact on the regional groundwater.
Keywords: гидрогеология; Кузбасс; метан; угольные пласты; гидродинамические расчеты; подземные воды; горные работы